Customer Commitment as a Mediating Variable between Corporate Brand Image and Customer Loyalty - Tu, Yu-Te; ., Yu-Yi Chang (Journal of Education and Vocational Research, 2014)
Research has shown that corporate image is an important determinant of customer loyalty. Having a positive corporate brand image helps companies achieve performance goals, such as higher sales, whereas having a poor brand image can be disastrous because it can cause companies to lose customers. A strong brand with high equity will have a large number of committed customers, many of whom will have frequent and ongoing interaction and communication with the company owning the brand. Customer commitment to a brand stems from trust in the brand, shared values with the company owning the brand, and a belief that it would be difficult to find other brands that could provide same value. Customer loyalty also encourages companies to cooperate with their business partners to preserve their investment in the business relationship. Committed customers have a more positive impression of their relationship with the company and indicate strong intentions to remain in the relationship. The researchers conducted a survey among respondents from the automobile sector in Taiwan, and obtained 170 usable responses. The researchers designed the questionnaires to analyze normality, convergent, and discriminant validities by using the structural equation model of PASW 18 and AMOS 18.0. The research found that commitment is a partial mediator between corporate brand image and customer loyalty. Future studies might measure other dimensions to test their mediating effect on customer loyalty, and these studies might use different designs to examine the mediator effect posited by various theories, such as trust added, to explore other determinants of loyalty. Such research can inform decisions made to increase and maintain long-term customer satisfaction.